THE BEHAVIOUR OF THE MOLLUCAN MEGAPODE, EULIPOA WALLACEI CAVES:MEGAPODIDAE) IN NESTING GROUNDS - C. J. HEIJ (BRIN Publishing (Penerbit BRIN), 1997)
The moluccan -megapode, Eulipoa wallacei is the only hole digging megapode in the island of Haruku. The birds lay eggs in a communal nesting ground exposed to the heat of the sun. The eggs collected between 1987 and 1995 showed an increase in number. The factors influencing the increase in number were not fully known, but it seems the social economic activities of the local peoples influenced the intensity of searching the eggs. There were also differences in number of eggs collected in wet and dry season. The birds lay eggs at the depth of 60-90 CIII in soil, the average eggs length 78.1 mm, average width 48.9 mm. The average soil temperature 27Â° - 35Â°C. The eggs in the incubation boxes resulted in 92.7% hatchlings, average incubation time 74.2 days, and the hatchlings found on the soil surface have an average weight of 57 gr. The behaviour of the bird in detail is indicated.